Emotion Regulation and the Experience of Future Negative Mood: The Importance of Assessing Social Support - d’Arbeloff, Tracy C.; Freedy, Katherine R.; Knodt, Annchen R.; Radtke, Spenser R.; Brigidi, Bartholomew D.; Hariri, Ahmad R. (Frontiers in Psychology, 2018)
Emotion regulation refers to the use of various strategies, such as cognitive reappraisal and expressive suppression, to help manage our negative experiences, emotions, and thoughts. Although such emotion regulation often occurs within broader social dynamics and interactions, little is known about how social contexts interact with specific regulation strategies to shape the experience of negative emotions. Using data from 544 young adult university students, we provide initial evidence that habitual use of cognitive reappraisal is associated with lower future experience of depression and anxiety primarily through higher perceived social support. In contrast, expressive suppression is associated with higher future depression and anxiety primarily through lower perceived social support. These patterns are consistent with the importance of interpersonal influences on emotion regulation and suggest that assessment of social support can help elucidate the mechanisms of successfully regulating negative mood.